BS EN IEC 60747-5-16. Semiconductor devices. Part 5-16. Optoelectronic devices. Light emitting diodes. Test method of the flat-band voltage based on the photocurrent spectroscopy (7th December 2021) - British Standards Institution,
No abstract available